The Impact of Innovation and Government Intervention on the Performance of Micro, Small and Medium Enterprises - Miar Miar (Shirkah: Journal of Economics and Business, 2024)
During the COVID-19 pandemic, Micro, Small and Medium Enterprises (MSMEs) experienced a decline in performance due to low product demand. Therefore, various efforts need to be undertaken to enhance MSMEs' performance in Indonesia. Addressing this issue, this research aims to examine the influence of innovation and government intervention in improving the performance of SMEs in Indonesia. The study employs a quantitative approach with a population of MSME actors in Central Kalimantan, a province of Indonesia. Through proportional random sampling, 356 SME operators were identified as respondents for this study. Data were collected using a survey method and analyzed using simple and multiple linear regression. The results indicate that innovation and government intervention have a positive and significant impact on improving MSMEs' performance both partially and simultaneously. Therefore, this research implies that the more MSMEs engage in innovation and with government involvement in efforts to support MSME development, the greater the opportunity to enhance MSME performance in Indonesia.